Parametric Analysis of Macro-Geometrical Deviations in Dry Turning of UNS A97075 (Al-Zn) Alloy. - Martín-Béjar, Sergio; Trujillo-Vilches, Francisco Javier; Bermudo-Gamboa, Carolina; Sevilla-Hurtado, Lorenzo (MDPI, 2019)
Macro-geometrical deviations play a very important role in the functionality and reliability of structural parts for aircraft. The use of environmentally friendly techniques, such as dry machining, may negatively affect these deviations. Despite its importance, there is a lack of research that analyzes them as a function of the cutting parameters in the case of aluminum alloys for aeronautical purpose. In this work, the cutting speed and feed influence on several macro- geometrical deviations (parallelism, straightness, circular run-out, roundness, concentricity, total circular run-out and cylindricity) in dry turning of UNS A97075 alloy was analyzed. The main novelty of this work lies in the use of high slenderness parts used in further fatigue tests. The results showed that feed seems to be the most influential parameter in most of the deviations studied. In addition, the parts with lower rigidity exhibited higher sensitivity to change with the cutting parameters. Finally, different parametric models were proposed to obtain the geometrical deviations as a function of the cutting parameters.
Keywords: Torneado; Aleaciones; Ciencia de los materiales; UNS A97075; Dry turning; Straightness; Parallelism; Roundness; Concentricity; Circular run-out; Total run-out; Cylindricity; Surface integrity